2021
DOI: 10.1177/0266666921999749
|View full text |Cite
|
Sign up to set email alerts
|

Has the Internet increased FDI, economic growth, and trade? Evidence from Asian economies

Abstract: This study examines the causal relationship between the Internet and economic factors in Asian economies between 1997 and 2017. The economic factors consist of gross domestic product (GDP), foreign direct investment (FDI), imports, and exports. A comparative analysis of East, South, and Western Asia was conducted using a panel vector autoregressive model. The findings show bidirectional causality between FDI and Internet use in South Asia, unidirectional causality from Internet use to FDI in East Asia, and uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…He believed that such a “multiple unity” was developed in a long-term historical process and proposed cultural self-consciousness. He conducted numerous social and historical surveys of ethnic minorities and put forward the theories of ”small town construction,” “township enterprises,” “Southern Jiangsu model,” and “Wenzhou model” [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He believed that such a “multiple unity” was developed in a long-term historical process and proposed cultural self-consciousness. He conducted numerous social and historical surveys of ethnic minorities and put forward the theories of ”small town construction,” “township enterprises,” “Southern Jiangsu model,” and “Wenzhou model” [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, Ozcan and Nath (2016) explored the role of ICT on international trade and discovered that causation may run in the opposite direction, i.e., export or import may increase ICT use. Aside from that, previous research has found unidirectional causality between exports and Internet use in East Asia, as well as unidirectional causality between Internet use and exports in South Asia, but no influence in Western Asia (Yin & Choi, 2021). Freund and Weinhold (2002), identified a causal link between the Internet and international service commerce while looking at the association between Internet adoption and international service trade.…”
Section: Literaratur Reviewmentioning
confidence: 96%
“…Hence, a study of e-commerce on trade has practical importance in developing and boosting international trade. Yin and Choi [ 4 ] discovered that e-commerce is a kind of tech which can increase/improve productivity in many ways, simultaneously, which can be used as a tool to lower the cost.…”
Section: Literature Reviewmentioning
confidence: 99%